Major venom proteins of the fire ant Solenopsis invicta: insights into possible pheromone‐binding function from mass spectrometric analysis. Issue 4 (15th April 2018) - Das, T.; Alabi, I.; Colley, M.; Yan, F.; Griffith, W.; Bach, S.; Weintraub, S. T.; Renthal, R.
Abstract: Proteins in the venom of the fire ant Solenopsis invicta have been suggested to function in pheromone binding. Venom from queens and workers contains different isoforms of these proteins, consistent with the differing pheromones they secrete, but questions remain about the venom protein composition and glandular source. We found that the queen venom contains a previously uncharacterized pheromone‐binding protein paralogue known as Sol i 2X1. Using imaging mass spectrometry, we located the main venom proteins in the poison sac, implying that pheromones might have to compete with venom alkaloids for binding. Using the known structure of the worker venom protein Sol i 2w, we generated three‐dimensional homology models of the worker venom protein Sol i 4.02, and of the two main venom proteins in queens and female alates, Sol i 2q and Sol i 2X1. Surprisingly, the models show that the proteins have relatively small internal hydrophobic binding pockets that are blocked by about 10 amino acids of the C‐terminal region. For these proteins to function as carriers of hydrophobic ligands, a conformational change would be required to displace the C‐terminal region, somewhat like the mechanism known to occur in the silk moth pheromone‐binding protein.